2007
DOI: 10.1242/jeb.02744
|View full text |Cite
|
Sign up to set email alerts
|

Spectral properties of identified polarized-light sensitive interneurons in the brain of the desert locustSchistocerca gregaria

Abstract: SUMMARY Many migrating animals employ a celestial compass mechanism for spatial navigation. Behavioral experiments in bees and ants have shown that sun compass navigation may rely on the spectral gradient in the sky as well as on the pattern of sky polarization. While polarized-light sensitive interneurons(POL neurons) have been identified in the brain of several insect species,there are at present no data on the neural basis of coding the spectral gradient of the sky. In the present study we ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
62
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 68 publications
(65 citation statements)
references
References 34 publications
3
62
0
Order By: Relevance
“…Both constitute the largest AOTu volume and are composed of two subunits (outer and inner lobes in locusts; MU-VL and MU-DL in honeybees). Our results suggest a spatial information content at the MU inter-tubercle output, and likewise, upper unit interneurons in locusts respond in a strongly stimulus position-dependent manner (Pfeiffer and Homberg, 2002;Pfeiffer et al, 2005;Kinoshita et al, 2007). We thus believe that this bi-lobed major AOTu compartment serves similar spatial processing functions in honeybees and locusts.…”
Section: Aotu Function In a Physiological And Behavioral Contextmentioning
confidence: 51%
See 2 more Smart Citations
“…Both constitute the largest AOTu volume and are composed of two subunits (outer and inner lobes in locusts; MU-VL and MU-DL in honeybees). Our results suggest a spatial information content at the MU inter-tubercle output, and likewise, upper unit interneurons in locusts respond in a strongly stimulus position-dependent manner (Pfeiffer and Homberg, 2002;Pfeiffer et al, 2005;Kinoshita et al, 2007). We thus believe that this bi-lobed major AOTu compartment serves similar spatial processing functions in honeybees and locusts.…”
Section: Aotu Function In a Physiological And Behavioral Contextmentioning
confidence: 51%
“…The VLU of the honeybee AOTu shows remarkable similarity with the lower unit of the locust AOTu (Homberg et al, 2003), which processes polarized light information and conveys it via the LAL to the central body (Pfeiffer et al, 2005;Homberg 2007, 2009;Kinoshita et al, 2007). Both are positioned ventrodorsally and posterior to the more prominent AOTu unit (MU in honeybees; upper unit in locusts) and receive input from the dorsal medulla.…”
Section: Aotu Function In a Physiological And Behavioral Contextmentioning
confidence: 99%
See 1 more Smart Citation
“…Including the outlier gives the statistics R adj = 0.47 and p = 0.04 which still is 439 significant, but not surprisingly with a much lower R adj value. There is evidence that 440 polarization cues and possibly the correlated color gradients can be suppressed at high 441 irradiances (Kinoshita et al, 2007) and in such case, the model would actually predict 442 normal orientation. At a constant wavelength of 565 nm there was good fit of the model to 443 the r-values with R adj = 0.74 and p < 0.0001 (Fig.…”
Section: Predictions On the Concentration Of Orientation (R-value) 312mentioning
confidence: 99%
“…It has been suggested that light in the blue or mid wavelength range may serve as 182 some sort of reference color in a color gradient compass (Kinoshita et al, 2007). In that 183 case Eq.…”
mentioning
confidence: 99%